Penelitian untuk mendapatkan kekerasan dan kuat sobek kompon bantalan karet dermaga yang memenuhi SII - Prayitno Prayitno; Hadi Musthofa (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1994)
The aim of the research was to find out the dock vender compound which have optimum hardness and tearing resistance. The research was done by using standar compound for dock vender in which the carbon black as a filler was varied at 40; 45: 50; 55; 60; 65 and 70 parts for every 100 parts of natural rubber. Testing results show that optimum hardness was found at a compound with 55 parts of carbon black by the value of 60.40 shore A, whereas the tearing resistance show that there are no significant defferences by variation of carbon black. Optimum tearing resistance was given by the compound with 45 parts of carbon black.